Diabetes management in people living with dementia in Japan: a qualitative exploration. Issue 5 (11th July 2022) - KM, Saif‐Ur‐Rahman; Hirano, Yukiko; Hirakawa, Yoshihisa; Yatsuya, Hiroshi
Abstract : Background: Dementia and diabetes are highly prevalent among the older society in Japan. People living with dementia (PLWD) often face hurdles in managing diabetes. This study explored the perspectives of healthcare providers in Japan regarding diabetes management in PLWD. Methods: We conducted a qualitative study using in‐depth interviews as a data collection method. A total of 15 physicians and nurses were interviewed. A qualitative content analysis of the codes was performed to generate the themes. Results: The major themes focused on the management of medications/therapeutic regimen, difficulties of continuing health care, emotional aspects of PLWD for adherence to lifestyle modification, and varying direction and degree of family support for diabetes care. Conclusion: PLWD in Japan face challenges in medication management, food restriction, and lifestyle modification. Policies to engage home visit care workers in medication management, consideration of the emotional aspect of PLWD, and utilisation of social support might help in the proper management of diabetes in PLWD.